2019
DOI: 10.1002/slct.201803891
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of 4‐Chlorophenol Using Glassy Carbon Electrodes Modified with Thulium Double‐Decker Phthalocyanine Salts

Abstract: This paper presents newly developed electrochemical sensors based on green and blue lanthanide double‐decker phthalocyanines (LnPc2), with the green LnPc2 derivative referred to as 2 a while the blue counterpart is designated 2 b. The modified glassy carbon electrode (GCE) based on the blue LnPc2 complex is referred to as 2 b‐GCE while that which is based on the green LnPc2 complex is named 2 a‐GCE. The oxidation of 4‐chlorophenol is extensively investigated and found to differ from one modified electrode to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…[46][47][48][49][50][51][52] Currently, most of the electrolytes used in this field are phosphate or sodium acetateacetic acid buffer solution. [53][54][55][56][57][58][59] The reference electrode offers a constant potential so as to control and adjust the working electrode potential accurately, which facilitates the quantitative analysis of the electrochemical system. In electrochemical sensors, the Ag/AgCl electrode and saturated calomel electrode (SCE) are the most commonly used reference electrodes.…”
Section: Electrochemical Cell Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…[46][47][48][49][50][51][52] Currently, most of the electrolytes used in this field are phosphate or sodium acetateacetic acid buffer solution. [53][54][55][56][57][58][59] The reference electrode offers a constant potential so as to control and adjust the working electrode potential accurately, which facilitates the quantitative analysis of the electrochemical system. In electrochemical sensors, the Ag/AgCl electrode and saturated calomel electrode (SCE) are the most commonly used reference electrodes.…”
Section: Electrochemical Cell Configurationmentioning
confidence: 99%
“…6d, Sekhosana et al modified GCE surfaces with a thulium double-decker phthalocyanine (TmPcs), which possesses great electrocatalytic activity. 53 The surface modification resulted in the enhancement of the LSV response towards 4-CP, with a LOD of 0.0416 mM. 53 Metallophthalocyanines can also form a bimetallic system suitable for surface modification of electrodes.…”
Section: Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The blue form stands for [(Pc 2À )Tm III (Pc 2À )] À (i.e., both the HOMO and LUMO are fully filled), with its overall charge compensated by a hexadecyltrimethylammonium cation, and responds better to oxidizing analytes, while the green form [(Pc À1 )Tm III (Pc 2À )] with one electron hole prefers reducing analytes. The authors discovered that the blue-GCE demonstrated a lower peak potential of 0.88 V vs. Ag|AgCl, a higher catalytic current of 593 mA, and apparent sensitivity towards the presence of 4-chlorophenol with a lowest detection limit of 4.16 Â 10 À8 M. 354 6.1.4 Temperature. Temperature-dependent lanthanide luminescence is a well-known physical phenomenon that can be exploited for thermosensing.…”
Section: Sensing and Biomedical Applicationsmentioning
confidence: 99%
“…Such simpler LnPc 2 complexes have not been used as an electrochemical sensor for PA before and are reported for the first time in this manuscript. LnPc 2 complexes are superior electrochemically active materials and exhibit small first oxidation minus first reduction difference [32][33][34][35][36][37][38][39] which depicts the effective electron transfer compared to lanthanidebased monophthalocyaninato counterparts, [39] hence their application in electronics and electrochemistry and as ambipolar organic field-effect transistors. LnPc 2 complexes whose electrocatalytic behavior is investigated herein are highly soluble in nonpolar solvents due to the tert-butyl bearing substituents, hence the employment of dichloromethane as a solvent when modifying the surface of GCE.…”
Section: Introductionmentioning
confidence: 99%